2017
DOI: 10.1016/j.eurpolymj.2017.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Graphene derivatives in responsive hydrogels: Effect of concentration and surface chemistry

Abstract: Reduced graphene oxide (RGO) containing composite hydrogels, based on poly(Nisopropylacrylamide) (PNIPA) were prepared by two different methods: i) by incorporating RGO directly into the polymer matrix; ii) applying a post-synthesis reduction of the grapheneoxide (GO) already incorporated into the polymer. The samples were compared by various microscopic (small angle neutron scattering, differential scanning calorimetry, 1 H NMR spectroscopy, thermogravimetry) and macroscopic (kinetic and equilibrium swelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…First, they can mechanically reinforce the hydrogel network and tune the elasticity of the hydrogel. For example, two-dimensional GO nanosheets [65,68,[72][73][74] or nano-clays [35,70] have been incorporated within PNIPAM hydrogels, thereby effectively modulating their mechanical properties. In the work of Berke et al [72], GO platelets were incorporated into the PNIPAM network by using chain nucleation, which resulted in a hypernodal structure of the PNIPAM gel ( Figure 1).…”
Section: General Strategies For Tuning the Properties Of The Pnipam-bmentioning
confidence: 99%
See 1 more Smart Citation
“…First, they can mechanically reinforce the hydrogel network and tune the elasticity of the hydrogel. For example, two-dimensional GO nanosheets [65,68,[72][73][74] or nano-clays [35,70] have been incorporated within PNIPAM hydrogels, thereby effectively modulating their mechanical properties. In the work of Berke et al [72], GO platelets were incorporated into the PNIPAM network by using chain nucleation, which resulted in a hypernodal structure of the PNIPAM gel ( Figure 1).…”
Section: General Strategies For Tuning the Properties Of The Pnipam-bmentioning
confidence: 99%
“…Superparamagnetic iron oxide NPs have also been incorporated into PNIPAM-based hydrogels to enable a magnetic response, which can achieve drug release through remote control with an oscillating magnetic field [71]. Moreover, by adjusting the size of the nanofillers as well as their physical/chemical interactions with the polymeric network, the phase transition temperature of the hydrogel and the responsive speed can also be effectively modulated [73,74,76]. Very recently Czakkel et al gave a comprehensive review about the effect of graphene-derivatives on the responsivity of PNIPAM-based nanocomposites [65].…”
Section: General Strategies For Tuning the Properties Of The Pnipam-bmentioning
confidence: 99%
“…It is also confirmed that the GO is well distributed in the matrix due to its high oxygen content. The C/O ratio of this GO, determined by XPS, was 1.8 [23].…”
Section: Results and Discussion 31 Characterization Of The Polymer Gelsmentioning
confidence: 93%
“…A felületkémiában keresendõ a magyarázata a grafén részecskék pH-érzékeny ülepedési tulajdonságainak 8 , alakváltozásának 9 , pH-val szabályozható fém nanorészecske megkötõ képességének 10 . A szén nanorészecskék felületkémiájuktól és alakjuktól képesek befolyásolni reszponzív lágygél kompozitokban azok hõmérsékletváltozásra vagy IR besugárzásra adott válaszát is 11,12 .…”
Section: áBra a Schay-nagy Féle Izotermaeloszlás Elsõ Közlése A Bme Punclassified